192k views
5 votes
Look at pic and answer pls

Look at pic and answer pls-example-1
User Scooterman
by
5.2k points

1 Answer

2 votes

(a)
x^(-5)

(b)
3x^(-7)

(c)
$(4)/(3)x^4

Solution:

To write each of the given expression in the form
ax^n:

(a)
(x^3)/(x^8)

Using exponential rule:
(a^x)/(a^y)=a^(x-y)


$(x^3)/(x^8)=x^(3-8)


$(x^3)/(x^8)=x^(-5)

(b)
(6x)/(2x^8)

Divide numerator and denominator by the common factor 2, we get


$(6x)/(2x^8)=(3x)/(x^8)

Using exponential rule:
(a^x)/(a^y)=a^(x-y)


$=3x^(1-8)


$(6x)/(2x^8) =3x^(-7)

(c)
(28x^6)/(21x^2)

Divide numerator and denominator by the common factor 7, we get


$(28x^6)/(21x^2)=(4x^6)/(3x^2)

Using exponential rule:
(a^x)/(a^y)=a^(x-y)


$=(4)/(3)x^(6-2)


$(28x^6)/(21x^2)=(4)/(3)x^4

User Gyan
by
4.4k points